2018
DOI: 10.14712/23362936.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Etiologic Agents of the Pertussis-like Syndrome in Children by Real-time PCR Method

Abstract: The aim of this study was to recognize the identity and frequency of etiologic agents of the pertussis-like syndrome in children < 2 years of age. A cross-sectional hospital-based study conducted from August 2014 to August 2015. All children < 2 years of age (n=100) who were suspected as pertussis infected were enrolled in this study and tested for Bordetella pertussis, adenovirus (Adv), respiratory syncytial virus (RSV), human metapneumovirus (hMPV), and influenza virus A (INF-A) by real-time PCR techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(27 reference statements)
0
8
1
Order By: Relevance
“…Previous studies have shown that pertussis infection in children sometimes mimics viral RTIs, especially in infants (6,27,35). In our study, there were no significant differences regarding the clinical symptoms between the two groups.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have shown that pertussis infection in children sometimes mimics viral RTIs, especially in infants (6,27,35). In our study, there were no significant differences regarding the clinical symptoms between the two groups.…”
Section: Discussioncontrasting
confidence: 60%
“…The FilmArray Respiratory Panel (FilmArray RP, v1.7) is able to detect 16 viral and 3 atypical respiratory pathogens, including B. pertussis, in a single test, which requires only 5 min of hands-on time and 65 min of instrument time (32). The multiplexed nature of this test enables the rapid differentiation of B. pertussis from other viruses that also cause pertussis-like syndrome, such as RSV, Adv and parainfluenza 3 (Para 3) (33)(34)(35). In addition, this method provides co-infection information for pertussisinfected patients, which may have underlying clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 232 children with median age of three years who presented with pertussis-like disease clinic, nasopharyngeal swab samples taken from patients were evaluated by PCR; In 9.9% of patients, hMPV was found to be positive alone and no co-infection was observed (9). In Iran between 2014 and 2015, a study that nasopharyngeal swab specimens were taken from 100 patients who applied to hospital with the symptoms of pertussis-like disease under two years of age and evalauted with PCR has showed that the incidence of hMPV was reported to be 10% and it did not accompany other infections (10).…”
Section: Discussionmentioning
confidence: 99%
“…Bordetella causes this respiratory disease. Bordetella pertussis is a small Gram-negative pathogen (2,3).…”
Section: Introductionmentioning
confidence: 99%